2000
DOI: 10.1038/sj.jp.7200365
|View full text |Cite
|
Sign up to set email alerts
|

Pumps for Peanuts: Leveling the Field in the Neonatal Intensive Care Unit

Abstract: In the United States, it is tragic and unnecessary that infants who would benefit most from human milk are least likely to receive it. Poor women, and particularly women of color, breastfeed their infants at a lower rate than other groups. National data from 1995 indicate that 60% of women in the United States initiate breastfeeding; however, among inner-city women, the rate is Ͻ40%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…45 Obtaining an electric breast pump for use after hospital discharge was a challenge for many mothers. Some NICUs provide hospital-grade electric pumps free of charge to mothers for the duration of their infant's hospitalization, 20,23 and some hospitals bill the mothers' insurance for pumps (personal communication, Greta Blythe, May 2008). This is a critical aspect of lactation support and should be of highest priority for NICU lactation programs.…”
Section: Discussionmentioning
confidence: 99%
“…45 Obtaining an electric breast pump for use after hospital discharge was a challenge for many mothers. Some NICUs provide hospital-grade electric pumps free of charge to mothers for the duration of their infant's hospitalization, 20,23 and some hospitals bill the mothers' insurance for pumps (personal communication, Greta Blythe, May 2008). This is a critical aspect of lactation support and should be of highest priority for NICU lactation programs.…”
Section: Discussionmentioning
confidence: 99%
“…12 Infant feeding decisions are in many ways also a function of economic opportunity, because while pumping is cheaper than formula over the long haul, formula is cheaper at any single point of purchase. The Boston-based pilot project 'Pumps for Peanuts', which sought to provide subsidies for pumps so that lower-income families who had babies in a neonatal intensive care unit could purchase pumps, found that economics played a large role in infant feeding choices (Phillipp et al, 2000). One lactation consultant noted that 'for many of these families the choice they quietly faced was paying for a breast pump or meeting a basic need such as food, rent, or heat for the rest of their family' (Philipp et al, 2000, p. 250).…”
Section: Discussionmentioning
confidence: 99%
“…To initiate lactation for a VLBW infant, mothers must pay between $90 and $150 for the first month's BPRF and the purchase of the BPCK. Most payers and institutions do not reimburse or pay these costs, so they are borne by the mothers 2024. This initial cost can be prohibitive because preterm birth means other unexpected expenses (e.g., increased insurance co-payments, hospital parking fees, lost wages).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, access to adequate amounts of HM from the infant's own mother should be a priority in the neonatal intensive care unit (NICU). However, the basic lactation equipment that these mothers need—a hospital-grade electric breast pump and a pump collection kit19,20—is not routinely reimbursed by public and private third-party payers 21. Thus, these mothers must incur the cost for the breast pump and pump kit, an economic burden that translates into a barrier20,22 to providing HM for a VLBW infant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation